2022
DOI: 10.1111/jonm.13865
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, coping strategies and intention to leave the nursing profession: A cross‐sectional nationwide study in China

Abstract: Aims This study aims to investigate the association between stressors, coping strategies and intention to leave the nursing profession among nurses. Background Job stressors and coping strategies are believed to affect turnover intention among nurses, but no large‐scale study has been conducted on these associations in China yet. Method A cross‐sectional secondary analysis was conducted among 51,406 nurses from 1858 hospitals. Univariable and multivariable logistic regression analyses were carried out, and odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…The difference may be due to the timing of the survey in this study; nurses who had the intention to leave may have already left, thus yielding a sample with a lower intention to leave ( 60 ). In addition, our study also found that contract nurses had higher turnover intentions than tenured nurses, which is consistent with previous studies ( 61 ). Contract nurses are paid less and receive fewer benefits than tenured nurses even though they perform the same job duties.…”
Section: Discussionsupporting
confidence: 93%
“…The difference may be due to the timing of the survey in this study; nurses who had the intention to leave may have already left, thus yielding a sample with a lower intention to leave ( 60 ). In addition, our study also found that contract nurses had higher turnover intentions than tenured nurses, which is consistent with previous studies ( 61 ). Contract nurses are paid less and receive fewer benefits than tenured nurses even though they perform the same job duties.…”
Section: Discussionsupporting
confidence: 93%
“…The coping strategy involves individual behavioral methods of managing stress by adjusting physiological and emotional responses, reducing discomfort ( 26 , 27 ). The challenges and coping strategies faced by older adult nursing staff in China have been extensively discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace conflict with peers and managers also affects nurses' intention to continue working with their organization (Lee and Kim, 2020). Finally, workload and deficient resources also affect nurses' turnover intention (Wang et al, 2022). The role of the immediate boss in the nursing job has great significance for nurses (Hampton et al, 2019;Hell ın Gil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace conflict with peers and managers also affects nurses' intention to continue working with their organization (Lee and Kim, 2020). Finally, workload and deficient resources also affect nurses' turnover intention (Wang et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%